Thermodynamic assessment of the Mg-Pb and Mg-Bi systems using substitutional solution and associate models for the liquid phase - Zhang F.; Tang Y.; Hu B.; Liu S.; Du Y.; Zhang Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
By means of CALPHAD approach, thermodynamic assessments of the Mg-Pb and Mg-Bi systems were carried out based on the available experimental data including thermodynamic properties and phase equilibrium data. The liquid phase was described with both the substitutional solution model and the associate model, and two sets of self-consistent thermodynamic parameters for the Mg-Pb and Mg-Bi systems were obtained, respectively. It was found that the associate model can account for the experimental data more satisfactorily than the substitutional solution one, especially for the liquid phase with the short-range order behavior.